PENINGKATAN KAPASITAS GURU DI SONGSERM SASANA VITTAYA SCHOOL THAILAND DALAM PENGEMBANGAM MEDIA PEMBELAJARAN BERBASIS ICT - Effendi, Muh Saeful; Robi’in, Bambang; Ananta Tur, Ajar Pradika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract Songserm Sasana Vittaya School is an Islamic boarding school that prioritizes religious education and academic achievement. This school also equips students with skills such as arts, sports, and technology. The implementation of learning at Songserm Sasana Vittaya School varies greatly, especially in the use of information technology both as media and material sources. The need to utilize information technology is a demand and at the same time a challenge for this school. So far, the use of technology in supporting the teaching and learning process at Songserm Sasana Vittaya School, especially in developing ICT-based learning media, has not been optimal. The problem is that teaching staff (teachers) do not have sufficient abilities and skills to develop ICT-based learning media. This community service activity aims to increase the capacity of Songserm Sasana Vittaya School elementary school teachers to develop ICT-based learning media. This community service activity was carried out using an offline training method with the target partners being 26 SSVS elementary school teachers. This activity is carried out through the stages of socialization, training, and evaluation. This community service activity has given good impact in increasing the participants' knowledge regarding the development of ICT-based learning media by 30.76%. Participants' knowledge, which was originally from55.76%, increased to 86.52%. Abstrak Songserm Sasana Vittaya School merupakan sekolah pesantren yang mengedepankan pendidikan agama dan juga prestasi akademik. Sekolah ini juga membekali siswanya dalam ketrampilan seperti seni, olah raga, dan teknologi. Pelaksanaan pembelajaran di Songserm Sasana Vittaya School sangat bervariasi terutama dalam pemanfaatan teknologi informasi baik sebagai media ataupun sumber materi. Kebutuhan pemanfaatan teknologi informasi menjadi tuntutan dan sekaligus tantangan bagi sekolah ini. Sampai sejauh ini pemanfaatan teknologi dalam mendukung proses belajar mengajar di Songserm Sasana Vittaya School khususnya dalam pengembangan media pembalajaran berbasis ICT belum optimal. Permaslaahanya Tenaga pendidik (Guru) belum memiliki kemampuan dan ketrampilan yang memadai untuk dalam mengembangkan media pembelabaran berbasis ICT. Tujuan dari kegiatan pengabdian masyarakat ini adalah untuk meningkatkan kapasitas guru sekolah dasar Songserm Sasana Vittaya School dalam mengembangkan media pembelajaran berbasis ICT. Kegiatan pengabdian masyarakat ini dilakukan dengan metode pelatihan secara offline dengan sasaran mitra yaitu para guru sekolah dasar SSVS berjumlah 26 orang. Kegiatan ini dilaksanakan melalui tahapan sosialisasi, pelaksanaan pelatihan, dan evaluasi. Kegiatan pengabdian kepada masyarakat ini telah berjalan dengan baik dan dampak berupa peningkatan pengetahuan para peserta pelatihan mengenai pengembangan media pembelajaran berbasis ICT sebesar 30,76%. Pengetahuan mitra yang semula 55.76% meningkat menjadi 86,52%.